PERTUMBUHAN DAN HASIL TANAMAN BAWANG DAUN (Allium fistulosum L.) AKIBAT PEMBERIAN MIKROORGANISME LOKAL (MOL) PADA MEDIA YANG BERBEDA - Ayu Sufi Rochima N; Palupi Puspitorini; Jeka Widiatmanta (Universitas Islam Balitar, 2021)
This study aims to determine the influence of the combination of soil planting media, compost, husk charcoal, determine the influence of local microorganism concentrations and determine the interaction of the two on the growth and yield of leek plants. The research design used randomized block design arranged in factorial (RBD) with 2 factors. The first factor of the planting medium (M) is 4 combinations: soil (M0), soil: compost (M1), soil: husk charcoal (M2), and soil: compost: charcoal husk (M3). The second factor is the concentration of local microorganisms (P) there are 3 throws: 10 ml / l (P1), 15 ml / l (P2) and 20 ml / l (P3). The variables of total weight and consumption weight showed a significant interaction with the best treatment of M3P3.